(untitled) (Journal of University of Babylon for Engineering Sciences, 2022)
Urbanization led to significant changes in the properties of the land surface. That appends additional heat loads at the city, which threaten comfort and health of people. There is unclear understanding represent of the relationship between climate indicators and the features of the early virtual urban design. The research focused on simulation capability, and the affect in urban microclimate. It is assumed that the adoption of certain scenarios and strategies to mitigate the intensity of the UHI leads to the improvement of the local climate and reduce the impact of global warming. The aim is to show on the UHI methods simulation and the programs that supporting simulation and mitigate the effect UHI. UHI reviewed has been conducted the form of many studies, it resulted that all simulation methods were pass through the follow stages: modeling, Simulation and mitigation. Most of the literature reviewed shows that there are some key criteria that have been adopted as universal urban health coverage in cities, and that the first control component is city design.